Seed Dispersal and Frugivory: Ecology, Evolution and Conservation. Third International Symposium-Workshop on Frugivores and See 2002
DOI: 10.1079/9780851995250.0241
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of fruiting and food hoarding by rodents in neotropical forests: consequences for seed dispersal and seedling recruitment.

Abstract: This paper presents a general, annually based model for hoarding in neotropical forests inhabited by large caviomorph rodents. Data on the range of seed removal and predation-hoarding ratios for 4 large-seeded tree species in one neotropical rain forest are summarized. Based on these data, a model of seed hoarding in relation to fruit resource abundance is presented. The implications of the model to seed fate and seedling recruitment considering the recent literature on seed dispersal by neotropical rodents ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
0
4

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 0 publications
3
78
0
4
Order By: Relevance
“…JANSEN et al (2004) found that seed mass and masting fruiting were the major determinants of seed caching by acouchies -Myoprocta acouchy Erxleben, 1777 of Carapa procera DC., 1824 Meliaceae) in French Guiana. Our data does not show that intra-specific masting was an important factor to determine seed fate, since none of our studied species present fruit masting, but overall fruit availability may have been important (FORGET et al 2002, GENINI et al 2009). Nevertheless, we do not have information on seed fate on species that ripen during the season of fruit scarcity.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…JANSEN et al (2004) found that seed mass and masting fruiting were the major determinants of seed caching by acouchies -Myoprocta acouchy Erxleben, 1777 of Carapa procera DC., 1824 Meliaceae) in French Guiana. Our data does not show that intra-specific masting was an important factor to determine seed fate, since none of our studied species present fruit masting, but overall fruit availability may have been important (FORGET et al 2002, GENINI et al 2009). Nevertheless, we do not have information on seed fate on species that ripen during the season of fruit scarcity.…”
mentioning
confidence: 85%
“…The probability of seed dispersal by agoutis is affected by both seed availability and seed traits, such as seed mass and the presence of secondary compounds in the seeds (FORGET et al 2002, JANSEN et al 2004, GUIMARÃES et al 2003. However, most experiments on seed dispersal by caviomorph rodents have been done with large seeds and focused on seed mass variation within species (JANSEN et al 2004, but see FORGET et al 1998.…”
mentioning
confidence: 99%
“…Nos períodos de abundância de frutos, muitos frugívoros podem consumir as mesmas espécies, mas no período de escassez as dietas divergem (Forget et al, 2002), pois diferenças na morfologia do trato digestório permitem que as espécies utilizem diferentes alimentos, ou os mesmos alimentos de maneira diferente (Tutin et al, 1997).…”
Section: Discussão Geral E Implicações Para a Conservaçãounclassified
“…The seed and seedling ecology of Carapa has been well documented [16,29,41,[68][69][70][71]. Seeds are exclusively dispersed by scatterhoarding rodents, especially acouchi and agouti [72,73]. The peak season for scatter-hoarding-April to May [73]-coincides with the peak seed crop for several large-seeded tree species, such Carapa [74].…”
Section: Study Speciesmentioning
confidence: 99%
“…Seeds are exclusively dispersed by scatterhoarding rodents, especially acouchi and agouti [72,73]. The peak season for scatter-hoarding-April to May [73]-coincides with the peak seed crop for several large-seeded tree species, such Carapa [74]. Rodents act as dispersers by removing seeds from below parent trees, and burying the seeds as food reserves in shallow, spatially scattered caches in the topsoil, each cache containing a single seed.…”
Section: Study Speciesmentioning
confidence: 99%